Scientific description of the manuscripts of the treatise "Risala fi-s Siyasа" of Abu Nasr al-Farabi (Journal of Oriental Studies, 2022)
The article provides a scientific description of the manuscripts of the treatise of Second Teacher AbuNasr al-Farabi (260 AH/870 – 339 AH/950) "Risala fi-s Siyasa" (السیاسة في رسالة/ (Treatise on politics/. Italso provides information about the discovery of the manuscripts of the treatise preserved under differentnames in libraries and archives of the world and about their collection, publication and research anddates of copying.The first scientific edition of the treatise was published in two issues (No. 14, 15, 1901) of the journal"Al-Mashriq" (Al-MACHRIQ "المشرق ,("which started to be published at the beginning of the twentiethcentury. The manuscript was edited and published by the then editor-in-chief of the journal, the scholarLuis Scheiкo (1859-1927).During the writing the article, were used materials from the "Eastern Library" (Beirut), BibliotecaApostolica Vaticana (Vatican), Topkapı Sarayı Müzesi Kütüphanesi, Ayasofya, Süleymaniye Kütüphanesi(Turkey), sources of rare funds and archives of the Egyptian National Library (Dar al-Kutub al- Misriya)and The Institute of Arabic Manuscripts. In a scientific article, based on the cardinal changes in thedomastic Farabi studies in recent years (to form new directions in the study of al-Farabi's heritage, todetermine the manuscripts of the scientist's works, to collect the found manuscripts and to translate themfrom the original and republish, define scientific terms, draw new conclusions and etc.) research methodswere used such as historical-comparative, historical-typological, chronological, hermeneutic, sourcestudy and textological.Key words: heritage of Al-Farabi, manuscript, scientific description, archive, source study.